Evaluation of influence of factors of life-sustaining activity on the level from morbidity of leptospirosis in the example of the Chernivtsi region. - Hopko, N. V. (Medicni Perspektivi, 2018)
The relevance of leptospirosis is associated with its wide spread in many countries of the world, an increase in the number of severe forms of the disease, often with a fatal outcome, which determines its high medical, social and economic importance. In modern conditions, it is necessary to evaluate the influence of various factors on the incidence of leptospirosis through the use of a wide arsenal of statistical methods. Preventing epidemic growths is possible through effective preventive and anti-epidemic measures developed on the basis of epidemiological surveillance and risk assessment. In order to determine the relationship between the incidence rates of leptospirosis and the environmental factors, we conducted a study using regression analysis with subsequent correlation analysis. The study used data from the State Institution "ChernivtsiRegionalLaboratoryCenterof the Ministry of Health of Ukraine", as well as data from the State Statistics Service of Ukraine on social factors for 2008-2018. Given the results of multivariate regression analysis, the most significant factors that affect the incidence of leptospirosis were the infection of cattle, pigs, dogs, cats. The influence of migration processes on the incidence of leptospirosis is proved, which should be taken into account in reporting forms for further correlation analysis and optimization of the epidemiological surveillance system. Improving the system of epidemiological surveillance of leptospirosis by identifying elements in the information, diagnostic and management subsystems will facilitate timely intervention to make adequate management decisions.